GAMBARAN PAPARAN IKLAN OBAT SWAMEDIKASI DAN HUBUNGAN TINGKAT PENGETAHUAN TERHADAP PERILAKU SWAMEDIKASI SAKIT KEPALA - Muin, Fathul; Putri, Ardhia Paramesti Faisa (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
In order to take care of minor health issues without going to a doctor, self-medication is typical practice in the community. One of the most common health issues that people self-medicate with OTC medications is headache. There is a possibility that people's views and choices about medicine usage are impacted by the extensive exposure to drug advertisements in digital and electronic media. This study aims to examine the community’s experience with headache medication advertisements and analyze the relationship between knowledge level and self-medication behavior in Sleman Regency, Indonesia. The study used a cross-sectional design and a convenience sample of 159 people to administer an online questionnaire and gather data. To assess the correlation between the variables, descriptive statistics and a chi-square test were used. It was found that 68.6% of those who took the survey knew a lot about how to treat headaches on their own. There were significant correlations (p<0.05) between the amount of knowledge and the conduct of self-medication. The community had a high level of understanding and used proper self-medication practices. People with excellent information continued to exhibit logical behaviors while being exposed to medication commercials, which influenced their decision-making.